What role do bacteria play in persisting fistula formation in idiopathic and Crohn's anal fistula?. (March 2015) - Tozer, P. J.; Rayment, N.; Hart, A. L.; Daulatzai, N.; Murugananthan, A. U.; Whelan, K.; Phillips, R. K. S.
Abstract Aim The aetiology of Crohn's disease‐related anal fistula remains obscure. Microbiological, genetic and immunological factors are thought to play a role but are not well understood. The microbiota within anal fistula tracts has never been examined using molecular techniques. The present study aimed to characterize the microbiota in the tracts of patients with Crohn's and idiopathic anal fistula. Method Samples from the fistula tract and rectum of patients with Crohn's and idiopathic anal fistula were analysed using fluorescent in situ hybridization, Gram staining and scanning electron microscopy were performed to identify and quantify the bacteria present. Results Fifty‐one patients, including 20 with Crohn's anal fistula, 18 with idiopathic anal fistula and 13 with luminal Crohn's disease and no anal fistula, were recruited. Bacteria were not found in close association with the luminal surface of any of the anal fistula tracts. Conclusion Anal fistula tracts generally do not harbour high levels of mucosa‐associated microbiota. Crohn's anal fistulas do not seem to harbour specific bacteria. Alternative explanations for the persistence of anal fistula are needed.